GUISSE: A Graphical User Interface For Snippet Selection and Evaluation in Time Series Data - Fernandes, Guilherme; Gaspar, Lucas Peres; Cruz, Lívia Almada; Magalhães, Regis Pires; Macêdo, José Antônio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
Time series snippet discovery offers powerful tools for summarizing complex temporal data via representative subsequences. While advanced methods, such as Matrix Profile-based approaches and our RS4 (Restricted Search Space for Snippet Selection), achieve strong efficiency and pattern fidelity, their adoption remains limited by usability barriers. Existing algorithms typically produce raw numerical outputs that require technical expertise to interpret, and few accessible interfaces support configuration or visualization. In this demo, we present GUISSE, an interactive graphical interface for executing and evaluating snippet discovery algorithms. The platform enables flexible experimentation with RS4 and baseline methods, allowing users to configure clustering techniques, distance weightings, and snippet parameters. By bridging algorithmic execution with interactive exploration, GUISSE empowers a broad range of users to apply, interpret, and validate snippet discovery results without programming expertise, promoting transparent and reproducible time series summarization workflows.